Remarks on the documentation in OED3: cooking terms as a test case - Podhajecka, M (2010)
In the present paper I focus on the documentation in the third edition of the Oxford English Dictionary (henceforth, OED3). While the material of the first (OED1) and second (OED2) editions has often been hotly debated (e.g. Schäfer 1980, 1989; Willinsky 1994; McConchie 1997; Brewer 2006, 2007), studies on the newly-revised edition have so far been undertaken by the lexicographers only (e.g. Durkin 2002; Simpson 2004, Simpson, Weiner and Durkin 2004; Gilliver 2005). Nonetheless, even though the revision is a huge academic enterprise - and its results are truly amazing - OED3 documentation should no doubt be verified systematically to point out inevitable gaps and inconsistencies. It seems that Google Books, a gigantic online resource, will make such verification feasible; as my research has already shown, despite its numerous deficiencies, Google Books can be successfully "harnessed" for lexicological and lexicographic purposes (Podhajecka in press). To arrive at reliable results, I worked with headwords from OED3 letter sections revised to date(M-R), which were extracted automatically by means of the "search in definitions" option, "cookery" being used as the query keyword. Next, I excluded all the words and senses with the first attestation before 1750, because an overwhelming majority of Google Books texts come from the second half of the 18th century and later periods, and I took into account nominal senses only. The final research sample covered 92 headwords, most of which are loanwords reflecting foreign cuisines (e.g. masala, minceur, mirin, pain de campagne, ras malai). There are two major points to be raised. Firstly, some additional evidence deserves to be introduced into the dictionary, as there are a number of antedating quotations in Google Books―some of which push the first recorded occurrence by over a hundred years―that have been omitted by OED3 lexicographers. Regrettably, only a proportion of the quotations are verifiable (they come from full-text sources), while others may not be fully credible (they are available in the form of text snippets). No data has been found mainly for 20th-century senses of frequent lexical items (e.g. mark, pancake, purse), perhaps because I failed to come up with relevant Boolean expressions to limit the number of hits. Secondly, to help improve existing documentation, I offer suggestions concerning various aspects of the dictionary material, such as sense discrimination (e.g. masala, Napolitana, parcel, pastilla), classification of quotations(e.g. microwave, polonaise, portugaise), the treatment of full and shortened forms (e.g. mousseline/mousseline sauce, peel/candied peel), and the use of endophoric reference (e.g. pin/rolling pin). Occasionally, neither the use of lower-case and upper-case letter (e.g. nasi Padang) nor labelling (e.g. mochi, patty, rasgulla) is fully consistent. The effectiveness of the selection procedure is also an issue, inasmuch as a handful of headwords labelled Cookery have not been retrieved automatically (e.g. paste, pistou, pirog, poupiets, paupiette), which could be noticed thanks to the dictionary's rich cross-referencing structure.